A simulation system as alternative in the training of open sport skills - F.J. Moreno; A. Oña; M. Martínez; F. García (Asociación Española de Ciencias del Deporte, 2010)
This paper describes a computer-simulation system applied to sport sciences. This system is outcome of previous works in automatic systems of control of information. The features of this system and its applicability to learning of open motor skills are described. Open skills take place in an unpreditable environment and a computer is capable of recur it with digitalized images showed around the subjet in a laboratory. The results suggest that computer-simulation can be an effective way to train this motor skills. KEY WORDS: Computer simulation, automatic system, open motor skill.